FEASIBILITY ANALYSIS OF FOOTBRIDGE CONSTRUCTION WITH BILLBOARD SPACE IN SURABAYA: A CASE STUDY OF PT. XYZ - Indah Syafitri, Syaumi
The increasing number of motorized vehicles in Surabaya, which reached 5 million of registered units, has made pedestrians increasingly vulnerable to becoming victims of traffic accidents. Based on data from the Indonesian Police, more than 54% of pedestrian accidents are caused by crossing carelessly. To overcome this problem, the Surabaya government plans to collaborate with PT. XYZ, an advertising media company, to build a pedestrian bridge with billboard space. This collaboration will use a profit sharing system. This research aims to examine the feasibility of the project to build a pedestrian bridge with space billboards.